"Mała" i "duża" ojczyzna Łemków = The "great" and the "local" homeland of the Lemkos - Halczak, Bohdan (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The Lemkos population, dispersed in many countries, has its own one and common "local homeland" but various "greater homelands". For some of them Ukraine is their "great homeland" and for others the Carpathian Ruthenia. The difficulty the Lemkos experience with specifying their national identity is not unique in Europe. People who live in the borderlands of different cultures always find self-identification problematic. The Alsatians from the French-German borderland or the Silesians from the Polish-German borderland are further examples. Hence the relation with the "local homeland" is decisive in terms of identity.
Keywords: mała ojczyzna; ojczyzna; Łemkowie